2001
DOI: 10.1093/jn/131.2.354s
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Body Fat Distribution, Insulin Sensitivity and Islet β-Cell Function as Explanations for Metabolic Diversity

Abstract: Studies of metabolic processes have been enhanced by our understanding of the relationships among obesity, body fat distribution, insulin sensitivity and islet beta-cell function. Thus, we have learned that although insulin resistance is usually associated with obesity, even lean subjects can be insulin resistant due to the accumulation of visceral fat. Insulin sensitivity and beta-cell function are also intimately linked. The hyperbolic relationship between these two parameters explains why insulin-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
138
3
11

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(159 citation statements)
references
References 39 publications
7
138
3
11
Order By: Relevance
“…In this study, waist circumference, as a marker for abdominal fat distribution and fat mass, as a marker of general fat distribution, had similar associations with the cardiovascular risk factors. This is contrary to current evidence that visceral fat is a better marker of insulin resistance and cardiovascular risk than generalised fat [32]. Possible explanations for our findings include the fact that waist circumference reflects visceral, as well as deep and superficial subcutaneous fat.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, waist circumference, as a marker for abdominal fat distribution and fat mass, as a marker of general fat distribution, had similar associations with the cardiovascular risk factors. This is contrary to current evidence that visceral fat is a better marker of insulin resistance and cardiovascular risk than generalised fat [32]. Possible explanations for our findings include the fact that waist circumference reflects visceral, as well as deep and superficial subcutaneous fat.…”
Section: Discussioncontrasting
confidence: 99%
“…'Second' phase secretion has been shown to be lower than secretion occurring in non-diabetic controls at identical plasma glucose. It is of note, that insulin resistance itself has been shown to lead to 'upregulation' of the B-cell secretion (Tayek et al, 1997;Kahn et al, 2001), which underlines the importance of matching study subjects for obesity and age.…”
Section: Disturbances In Insulin Secretionmentioning
confidence: 99%
“…In studies in 283 non-diabetic subjects in whom insulin sensitivity and beta cell function were assessed with hyperglycemic clamps, we found that both are important for fasting and 2 h post OGTT plasma glucose levels, with tissue insulin sensitivity having the largest impact . One of the intrinsic problems is that insulin sensitivity has a marked impact on beta cell function (Tayek et al, 1997;Kahn et al, 2001); it may, therefore, remain cumbersome to dissect the impact of each of them.…”
Section: Impaired Glucose Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Seen from this perspective, it is not surprising that major genes conferring susceptibility to obesity or Type 2 diabetes are rare. Instead we encounter a complex patchwork of genetic and developmental influences upon insulin secretion, insulin resistance, fat deposition and inflammation [16]. The pioneers of diabetes genetics tended to view the body as a malfunctioning machine, on the assumption that correction of faulty genes or the pathways they controlled would restore a state of healthy normality.…”
mentioning
confidence: 99%